Sport for Development in International Relations - Svoboda Arnošt (Sciendo, 2021)
This article introduces the concept of sport for development and peace both as a theoretical notion and a part of the political-economical practice. Together with a brief definition and a historical overview, the main goal is to present the sport and development in the context of international relations, a network of stakeholders, practical implementation within major projects and its progressive inclusion into the development documents and strategies. Specifically, the article highlights the adoption of the concept by two major institutions, the United Nations and the International Olympic Committee as formal umbrella organisations. Furthermore, the role of the sport for development within the UN’s agenda of Sustainable Development Goals is elaborated. Since the topic is a frequent object of academic research and critical analysis, the article concludes with an outline of the commonly mentioned contested topics and critical debates which permeate both academic production and activities of international state and non-governmental organisations.